Prevalence of preoperative cognitive impairment among elderly thoracic surgery patients and association with postoperative delirium: a prospective observational study - Li, Fangfang; Miao, Mengrong; Li, Ningning; Zhou, Jun; Sun, Mingyang; Zhang, Jiaqiang (Frontiers in Human Neuroscience, 2023)
Background: Preoperative cognitive impairment (PCI) may increase the incidence of postoperative delirium (POD), yet screening for cognitive impairment is rarely performed. This study hypothesized that Mini-Cog for preoperative cognitive impairment screening predicts postoperative delirium. Methods: The prospective observational study recruited 153 elderly patients presenting for elective thoracic surgery. Cognitive function of these patients was screened using Mini-Cog preoperatively. We considered that patients with Mini-Cog scores ≤ 3 had cognitive impairment. Delirium was assessed using the Short CAM scale on postoperative days 1 to 5. Results: Of the 153 participants, 54 (35.3%) were assigned to the PCI group, and 99 (64.7%) were assigned to the Normal group. Place of residence, education level, and history of hypertension were significantly different between the two groups (P <0.05). 51 (33.3%) patients developed POD. Multifactorial analysis revealed that PCI (OR = 2.37, P = 0.028), older age (OR = 1.13, P = 0.009), ASA grade III (OR = 2.75, P = 0.012), and longer duration of anesthesia (OR = 1.01, P = 0.007) were associated with POD. Conclusion: PCI is strongly associated with POD. Mini-Cog could be recommended for screening PCI.